Oh, wie schön ist Panama - Janosch (Beltz & Gelberg, 1999)
Little Bear and Little Tiger leave their comfortable home behind to go in search of Panama, the land of their dreams, and end up in the most beautiful place in the world.
Keywords: Animals; Children's literature; German; Travel